2020
DOI: 10.2147/idr.s278891
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rapid Identification of KL49 <em>Acinetobacter baumannii</em> Associated with Clinical Mortality</p>

Abstract: Objective We aimed to establish a tool for rapid identification of KL49 Acinetobacter baumannii . Methods Based on the capsular polysaccharide (CPS) synthesis genes database, we investigated the distribution of K locus type 49 (KL49) genes in other KL types and established a rapid identification method for KL49. We collected 61 clinical carbapenem-resistant A. baumannii (CRAB) strains, identified KL49 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Though further work is needed to improve the predictive power of WGS for determination of CPS type, the database is a valuable tool for epidemiological studies. Our analysis showed that 17 KL represent a large proportion of the genome assemblies assessed in this study, which includes KL2, KL3/KL22 and KL49 that have been previously linked to increased virulence or poorer patient outcomes [8–10]. Though this may be due to bias in the dataset associated with strain sampling for outbreak studies, particularly the over-representation of genomes for GC2 isolates, new KL described here were each found in <1 % of genomes in the pool, indicating that the previous iteration of the database had captured the most common KL.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Though further work is needed to improve the predictive power of WGS for determination of CPS type, the database is a valuable tool for epidemiological studies. Our analysis showed that 17 KL represent a large proportion of the genome assemblies assessed in this study, which includes KL2, KL3/KL22 and KL49 that have been previously linked to increased virulence or poorer patient outcomes [8–10]. Though this may be due to bias in the dataset associated with strain sampling for outbreak studies, particularly the over-representation of genomes for GC2 isolates, new KL described here were each found in <1 % of genomes in the pool, indicating that the previous iteration of the database had captured the most common KL.…”
Section: Discussionmentioning
confidence: 80%
“…The genetics underlying the CPS type has also proven valuable as an epidemiological marker [3][4][5][6][7]. Finally, recent studies have associated some specific CPS types [8,9] or alterations in the CPS structure [10] with increased virulence. Hence, the determination of the specific type produced in problem strains is important in several areas.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to understand and track the epidemiology of AB have employed a variety of genotyping methods, revealing the pathogen’s sophisticated population dynamics. This includes exploring virulence traits such as capsular polysaccharide (KL) and the lipooligosaccharide outer core (OCL), which are substantively connected to AB’s pathogenic properties ( Deng et al, 2020 ; Li et al, 2020 ; Diep et al, 2023 ). The technological progress in whole-genome sequencing (WGS) has enriched genotyping capabilities, enabling more nuanced analysis through core genome multilocus sequence typing (cgMLST) or single nucleotide typing (SNP) for detailed typing and evolutionary studies.…”
Section: Introductionmentioning
confidence: 99%
“…An evident manifestation of CRAB’s genetic plasticity is its co-evolution toward both high virulence and drug resistance. One stark example is the KL49 AB type, similar in capsular polysaccharide type to the hypervirulent strain LAC-4 ( Zhou et al, 2018 ; Deng et al, 2020 ), which has been implicated in several death-related outbreaks across continents ( Valentine et al, 2008 ; Jones et al, 2015 ; Deng et al, 2020 ). Carbapenem-resistant hypervirulent AB (CR-hvAB) isolates with KL49 can cause fatal outcomes not only in immunodeficiency, but also in immunocompetent patients ( Jones et al, 2015 ; Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genetics underlying the CPS type has also proven valuable as an epidemiological marker [3][4][5][6][7]. Finally, recent studies have associated some specific CPS types [8,9] or alterations in the CPS structure [10] with increased virulence. Hence, the determination of the specific type produced in problem strains is important in several areas.…”
Section: Introductionmentioning
confidence: 99%